What makes us conscious of our own agency? And why the conscious versus unconscious representation distinction matters - Carruthers, Glenn (Frontiers in Human Neuroscience, 2014)
Existing accounts of the sense of agency tend to focus on the proximal causal history of the feeling. That is, they explain the sense of agency by describing the cognitive mechanism that causes the sense of agency to be elicited. However, it is possible to elicit an unconscious representation of one’s own agency that plays a different role in a cognitive system. I use the “occasionality problem” to suggest that taking this distinction seriously has potential theoretical pay-offs for this reason. We are faced, then, with a need to distinguish instances of the representation of one’s own agency in which the subject is aware of their sense of own agency from instances in which they are not. This corresponds to a specific instance of what Dennett calls the “Hard Question”: once the representation is elicited, then what happens? In other words, how is a representation of one's own agency used in a cognitive system when the subject is aware of it? How is this different from when the representation of own agency remains unconscious? This phrasing suggests a Functionalist answer to the Hard Question. I consider two single function hypotheses. First, perhaps the representation of own agency enters into the mechanisms of attention. This seems unlikely as, in general, attention is insufficient for awareness. Second, perhaps, a subject is aware of their sense of agency when it is available for verbal report. However, this seems inconsistent with evidence of a sense of agency in the great apes. Although these two single function views seem like dead ends, multifunction hypotheses such as the global workspace theory remain live options which we should consider. I close by considering a non-functionalist answer to the Hard Question: perhaps it is not a difference in the use to which the representation is put, but a difference in the nature of the representation itself. When it comes to the sense of agency, the Hard Question remains, but there are alternatives open to us.